Implementation of Simple Additive Weighting Method for Biomass Selection in IoT-Based Smart Stove - Tijaniyah (Transactions on Informatics and Data Science, 2024)
Technology is now needed most in everyday society. Many things have changed to become modern and sophisticated because of the role of technology. It helps with cooking food or drinks at home. The stove is one of the most critical components in the kitchen. A furnace can help cook food or beverages. The use of gas stoves is cost-intensive. Liquid petroleum gas (LPG) is a stove fuel often used by people for cooking. As cooking demands increase, gas consumption increases, causing gas expenses to become more and more costly. We make an intelligent or innovative stove with advantages. This smart stove is medium and portable so that it can be taken anywhere; besides that, this tool uses a supercapacitor to store the electric voltage generated in the heat of biomass combustion; this tool can generate electricity from biomass and solar cells. The selection of biomass types using the Simple Additive Weighting (SAW) method, namely wood or waste. The Internet of Things (IoT) is an information medium for the innovative stove process. In addition to cooking, this tool can turn on 1 LED lamp measuring 5-10 watts as a cellphone charger with as much as 5 volts or 60 minutes of charge time. The advantages of this intelligent stove are that it is beneficial to the community to reduce gas prices.